Actual paid cost of equity in construction - Tomáš Krulický; Veronika Machová; Ondřej Dvorák (Entrepreneurship and Sustainability Issues, 2022)
The value of the cost of equity capital is very important, both for all businesses and for investors, as it expresses the return on invested funds and is one of the most important factors in decision-making. The aim of the article is to determine the value of the actual paid costs of equity capital in the construction industry in 2016-2019. The used data from the Cribis / Albertina databases were processed using changes in the undistributed economic result of previous years and the economic result of the current accounting period. The results found show that the average cost of equity in the years 2016 - 2019 ranges from 29.35 % - 37.81 % and the median values range from 16.43 % - 24.24 %. The benefit of the presented results is primarily seen in their possibility of subsequent prediction of future costs of equity capital. A limitation of the research may be in the data used, for which it is appropriate when it is the most recent.